2018
DOI: 10.1038/s41598-018-26309-4
|View full text |Cite
|
Sign up to set email alerts
|

High electromechanical strain and enhanced temperature characteristics in lead-free (Na,Bi)TiO3–BaTiO3 thin films on Si substrates

Abstract: Here, we demonstrate the high electromechanical strain and enhanced temperature characteristics in the c-axis-oriented lead-free (Na,Bi)TiO3–BaTiO3 (NBT–BT) polycrystalline thin film prepared on Si substrates by rf magnetron sputtering. The effective transverse piezoelectric coefficient, e31*, estimated from the electromechanical strain measured under high electric field, reaches a high level of −12.5 C/m2, and is comparable to those of conventional Pb(Zr,Ti)O3 films. In-situ X-ray diffraction measurement and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…(b) e 31,eff values estimated from the BNT-BT films on the Si and SrTiO 3 substrates as a function of the measurement voltage (peak to peak). (c) e 31,eff values obtained in this study and those reported in previous studies. ,, …”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…(b) e 31,eff values estimated from the BNT-BT films on the Si and SrTiO 3 substrates as a function of the measurement voltage (peak to peak). (c) e 31,eff values obtained in this study and those reported in previous studies. ,, …”
Section: Resultssupporting
confidence: 67%
“…On the contrary, the dense structure of the present film on Si (Figure d) suggests that the large e 31,eff value would be related to the large d 33,f . Figure c compares the e 31,eff values of this study and previous studies on Pb-based perovskite films and Pb-free materials. ,, Note that the values in Figure c are obtained by various sample dimensions and methods. The e 31,eff value of the BNT-BT film obtained in this study is the highest among the Pb-free materials and even higher than those of most Pb-based films including Pb­(Zr, Ti)­O 3 , except for relaxor Pb­(Mg, Nb)-PbTiO 3 and Nb-doped Pb­(Zr, Ti)­O 3 films.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Figure 1B shows the distribution of the publications in the function of the synthesis process. As represented in Figure 1B, BNT thin films were mainly synthesized by chemical methods such as sol‐gel, CSD, and MOD 6,7 then by physical methods like PLD 8,9 or RF sputtering 10–14 . It is very surprising that sputtering has not been widely used in BNT synthesis, since this method has indeed been very successful for the PZT synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of environmentally friendly systems, nevertheless, the search for lead-free alternative materials has grown quickly over the last decades 4 7 . In particular, (BNT)-based materials have attracted great attention of scientists as a possible alternative to PZT-based piezoceramics 8 17 .…”
Section: Introductionmentioning
confidence: 99%